2005
DOI: 10.1159/000086760
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Three Hereditary Hemochromatosis Mutant Alleles in the Michigan Caucasian Population

Abstract: Objective: To investigate the prevalence in the Michigan non-Hispanic Caucasian population of the C282Y, H63D and S65C mutations in the HFE gene associated with hereditary hemochromatosis. Methods: Polymerase chain reaction and restriction fragment length polymorphism analysis were performed on 3,532 blood samples from newborn screening cards provided by the state of Michigan. Results: More than 30% of Michigan Caucasians carry one HFE mutation, while 6% have two mutations. The allele frequency of the C282Y mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
(81 reference statements)
1
12
1
Order By: Relevance
“…Although our sample population was not sufficiently large to provide adequate power to estimate the prevalence of homozygous HFE genotypes within racial subgroups, we were able to estimate the prevalence of homozygosity for the C282Y and H63D mutations in the combined population of 3989 California newborns. The respective C282Y and H63D allele frequencies of 5.5 and 13.4% found in our sample of White newborns reflect those previously reported in other U.S. non-Hispanic Caucasian populations [18,19,[28][29][30], as well as those recently published in a cohort of non-Hispanic Caucasian newborns in Michigan [31]. Despite similar HFE allele frequencies in these two populations of White newborns, the estimated prevalence of C282Y homozygotes was higher in the Michigan population of newborns (0.45%).…”
Section: Discussionsupporting
confidence: 91%
“…Although our sample population was not sufficiently large to provide adequate power to estimate the prevalence of homozygous HFE genotypes within racial subgroups, we were able to estimate the prevalence of homozygosity for the C282Y and H63D mutations in the combined population of 3989 California newborns. The respective C282Y and H63D allele frequencies of 5.5 and 13.4% found in our sample of White newborns reflect those previously reported in other U.S. non-Hispanic Caucasian populations [18,19,[28][29][30], as well as those recently published in a cohort of non-Hispanic Caucasian newborns in Michigan [31]. Despite similar HFE allele frequencies in these two populations of White newborns, the estimated prevalence of C282Y homozygotes was higher in the Michigan population of newborns (0.45%).…”
Section: Discussionsupporting
confidence: 91%
“…The C282Y mutation is present in 21 (15.2%) of the superdonors, slightly more than the reported 10 to 12 percent prevalence for the general Caucasian population. [9][10][11] This increase did not reach significance. None of the superdonors were homozygous for C282Y.…”
Section: The Hfe H63d Mutation Is Associated With Decreased Hepcidin mentioning
confidence: 74%
“…The H63D mutation is present in 31 (20.3%) superdonors, slightly less than the reported 24 percent prevalence for the general population. [9][10][11] Three of the 31 are homozygous for H63D and 3 are double heterozygous for the two mutations. Superdonors heterozygous for the H63D mutation had a significant reduction in hepcidin : ferritin ratio when compared to those without the mutation (p = 0.011; Fig.…”
Section: The Hfe H63d Mutation Is Associated With Decreased Hepcidin mentioning
confidence: 99%
“…Both mutations are more common in Caucasian patients. BARRY et al (6) , in a population based study, evaluated the prevalence of HFE mutations in newborns and noted that 30% of them carried a mutation in the gene and that 6% had two mutations. OLYNYK et al (28) , in another population based study, observed heterozygozity of C282Y mutation in 14.1% of cases.…”
Section: Discussionmentioning
confidence: 99%